Impact of Bradykinin Generation During Thrombolysis in Ischemic Stroke - Gauberti, Maxime; Potzeha, Fanny; Vivien, Denis; Martinez de Lizarrondo, Sara (Frontiers in Medicine, 2018)
Ischemic stroke is one of the leading causes of death and disability worldwide. Current medical management in the acute phase is based on the activation of the fibrinolytic cascade by intravenous injection of a plasminogen activator (such as tissue-type plasminogen activator, tPA) that promotes restauration of the cerebral blood flow and improves stroke outcome. Unfortunately, the use of tPA is associated with deleterious effects such as hemorrhagic transformation, symptomatic brain edema and angioedema, which limit the efficacy of this therapeutic strategy. Preclinical and clinical evidence suggests that intravenous thrombolysis generates large amounts of bradykinin, a peptide with potent pro-inflammatory and pro-edematous effects. This tPA-triggered generation of bradykinin could participate in the deleterious effects of thrombolysis and is a potential target to improve neurological outcome in tPA-treated patients. The present review aims at summarizing current evidence linking thrombolysis, bradykinin generation and neurovascular damage.